Sorbus calcicola (Rosaceae), a new species from Guangxi Province in China - Guo, Wei; Fan, Qiang; Jing, Huijuan; Hu, Xiu; Liao, Wenbo (Phytotaxa, 2016)
Sorbus calcicola W. B. Liao et W. Guo, a new narrow-range species from Guangxi Province in China, is described and illustrated here. Its relationships with morphologically close species S. pallescens, S. cuspidata and S. thibetica are also discussed. Phylogenetic analyses with nrITS gene along with a number of morphological features including leaves abaxially glabrous or tomentose in vein axils, lateral veins 5–6 pairs and corymbs inflorescence with only 3–7 flowers confirmed that it is a distinct new species.